Al Aman Mosque Philanthropy Fund Management in improving the society: Al Aman Mosque Philanthropy Fund Management in improving the society - Erwin Shofiyanti; Muhammad Kamal Muhtadi; Nur Kholis (University of Darussalam Gontor Press, 2023)
Objective: The large number of mosques in Indonesia does not guarantee prosperity for the mosque itself or for the community in general, the biggest problem exists because of an unprofessional management system. In this study, we will examine the management of philanthropic funds at the Al Aman Sidoarum Mosque and public opinion about how big the role of mosques is in boosting the economy. Method: Researchers used a qualitative descriptive method in the form of field research. The sample consisted of interviews with the chairman of the foundation, the chairman of the takmir and the chief of BUMM Al Aman mosque. And the questionnaire aimed at the surrounding community totaled 60 samples which were calculated using the tally method or frequency distribution. Findings: The results show that 70% of the community has experienced the mosque's efforts to improve the economy because the mosque management team has carried out the mandate properly and effectively, both in terms of quality and existing programs. Originality: According to the indicators of increasing the mosque's economy, it’s considered appropriate because accordance with the facts that the research results of the Al Aman mosque have completed four of them.